Influence of Different Pole Head Shapes on Motor Performance in Switched Reluctance Motors - POLAT, M. (Advances in Electrical and Computer Engineering, 2020)
The main reasons of the vibrations occurring in the stator of Switched Reluctance Motors (SRM) are the radial forces and they cause acoustic noise. This has an adverse effect on the performance of SRM. The aim of this study is to reduce radial forces by giving different geometric shapes to the pole heads and to investigate the effect of these pole shapes on the motor performance of SRM. In this study, the radial forces of four different SRMs having generally the same dimensions but different pole head shapes are calculated and compared with each other. In addition, the effects of different pole head shapes on the inductance curve and the torque ripple are investigated. To calculate the radial forces, torque and inductance values, ANSYS software is used which uses finite element method (FEM). After reshaping the pole heads, rotor position is changed with the increments of 1 degree from the unaligned to aligned position and the radial forces, torque and inductance values are calculated for each incremental position. According to the results, radial force is reduced about 19.03% at the rated current as compared to a standard SRM. However, torque ripple is observed to increase by about 3.29%.